2017
DOI: 10.1063/1.5006474
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic analysis of commercial hematite, magnetite, and their mixtures

Abstract: Magnetic techniques are suitable to detect iron oxides even in trace concentrations. However, since several iron oxides may be simultaneously present in natural and synthetic samples, mixtures of magnetic particles and magnetic interactions between grains can complicate magnetic signatures. Among the iron oxide minerals, hematite (α-Fe2O3) and magnetite (Fe3O4) are the most common. In this work, different commercial hematite powders, normally used as Fe precursor in laboratory synthesis of Fe-containing oxides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 19 publications
(26 reference statements)
0
40
0
3
Order By: Relevance
“…Magnetic property measurements ( Figure 4 ) indicate that all samples demonstrated significantly lower magnetization, M s , (less than ~20 emu/g calculated by dividing the magnetization by the mass of iron oxide NPs in the samples) at 5 K as compared to bulk ferromagnetic γ-Fe 2 O 3 (74 emu/g) and ferrimagnetic Fe 3 O 4 (84 emu/g) [ 42 ]; however, these were significantly higher than those of antiferromagnetic hematite α-Fe 2 O 3 (0.4 emu/g) [ 43 ] and goethite FeOOH (0.31 emu/g) [ 44 ] ( Figure 4 a). The low saturation magnetization can be a result of a surface spin disorder in ferro or ferrimagnetic NPs due to broken spins and canting of the surface spins; thus, the saturation requires a very high magnetic field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic property measurements ( Figure 4 ) indicate that all samples demonstrated significantly lower magnetization, M s , (less than ~20 emu/g calculated by dividing the magnetization by the mass of iron oxide NPs in the samples) at 5 K as compared to bulk ferromagnetic γ-Fe 2 O 3 (74 emu/g) and ferrimagnetic Fe 3 O 4 (84 emu/g) [ 42 ]; however, these were significantly higher than those of antiferromagnetic hematite α-Fe 2 O 3 (0.4 emu/g) [ 43 ] and goethite FeOOH (0.31 emu/g) [ 44 ] ( Figure 4 a). The low saturation magnetization can be a result of a surface spin disorder in ferro or ferrimagnetic NPs due to broken spins and canting of the surface spins; thus, the saturation requires a very high magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…However, at 300 K, the sample annealed at 450 °C has a higher magnetization over the whole applied magnetic field range ( Figure 4 b). Also, at 300 K, the sample with polymer and the sample that underwent UV ozone treatment show zero coercivities, while the sample after the thermal annealing shows coercivity of ~35 Oe, which could be due to structural defects [ 47 ] or indicative of some contribution of antiferromagnetic phase(s) that is (are) characterized by high coercivities [ 43 , 44 ]. The zero field cooling (ZFC) and field cooling (FC) data indicate the ferromagnetic response of all samples ( Figure 4 c).…”
Section: Resultsmentioning
confidence: 99%
“…At room temperature, i.e., above the Morin transition of Fe 2 O 3 , the moment in the (111) plane aligns at an angle giving weak ferromagnetism from the canting of spins, which shows up in the hysteresis plot . Fe 3 O 4 has inverse spinel structure with Fe 3+ ions aligned antiferromagnetically, and Fe 2+ ions aligned with the magnetic direction giving a net ferromagnetism much higher than that observed in Fe 2 O 3 . The in situ composite (Comp‐II) has a major contribution from Fe 2 O 3 hence exhibiting very similar saturation magnetism, while a decrease in the coercivity is observed in Figure (b).…”
Section: Resultsmentioning
confidence: 99%
“…Ahmadzadeh et al. (2018) concluded that it is challenging to identify hematite using hysteresis loops, FORCs, or thermal demagnetization when magnetite contributes more than 5 wt‐% to the mixture. Ahmadzadeh et al.…”
Section: Introductionmentioning
confidence: 99%